KAJIAN PREFERENSI PENGGUNA MODA TRANSPORTASI KERETA API LRT JAKARTA MENUJU STASIUN LRT VELODROME - Khansa Ramadianti; Nunung Widyaningsih (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2020)
The Government of Jakarta is trying to reduce the traffic volume by launching many new rail-based public transportation modes in this Jakarta Capital Region, one of them is Jakarta LRT. There are so many special things at the LRT Velodrome Station, for example the strategic location of Velodrome, the Jakarta International Velodrome stadium, integrated with Transjakarta transportation mode, etc. Even though the Jakarta LRT is the new transportation mode, but the Jakarta LRT only used by few people, because the route is still too short only 5,6 km (Pengangsaan Dua to Velodrome). So, this research discuss about the preference of passengers in using Jakarta LRT as the option for their daily transportation. The analysis of data obtained in this research by using the “Importance Performance Analysis” method, and analyzed the validity and reliability by using SPSS 24 program. The results of people’s preferences by using Jakarta LRT in this research are located in quadrant II that have a good performance on passengers satisfaction, so the performance must be maintained. And the items that needs to be improved for the efficiency and effectiveness are located in quadrant I that requires the high priority on its performance